Keselamatan, Kesehatan, dan Lingkungan untuk Meningkatkan Keterlibatan dan Produktivitas Karyawan - Irwansyah Irwansyah; M.Imam Maulana N; Eka Hardi Yudharsa (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the implementation of Safety, Health, and Environment (SHE) aspects in enhancing employee engagement, work flexibility, and productivity at PT Karuniatama Polypack. Methodology/approach: The research adopts a qualitative approach using data collection techniques such as in-depth interviews, field observations, and document analysis. The study focuses on understanding the integration of SHE practices within the company's work culture and their impact on human resource performance. Results/findings: The findings reveal that the implementation of SHE remains largely formalistic and has not been fully embedded in the organizational culture. The lack of employee involvement in SHE monitoring and communication results in low engagement levels, limited work flexibility, and decreased productivity due to poor safety awareness among employees. Conclusions: The study highlights the importance of holistic SHE integration to foster a safe, participatory, and productive work environment. A shift toward participatory managerial practices and safety-oriented organizational culture is recommended as a strategic approach to improving employee performance. Limitations: This research is limited to a single company and uses a qualitative design, which may restrict generalization. The findings are context-specific and may differ in organizations with varying SHE maturity levels or corporate cultures. Contribution: This study contributes to the body of knowledge on workplace safety and HR performance by emphasizing the strategic role of SHE in shaping employee behavior, engagement, and productivity. It also provides practical insights for manufacturing companies to improve SHE integration in daily operations.